"Buddy System": A Pedagogical Innovation to Promote Online Interaction - Espitia Cruz Martha Isabel; Kwinta Anna (Universidad Nacional de Colombia, 2013)
Recent technological development has created new pedagogical practices in the EFL classroom to maximize the time for students to use the language by considering online tools. Whilst working in a pedagogical context with new technologies, some educators were concerned with how online interaction in EFL content-based classes could be effectively promoted with university students. It was difficult to design and carry out online activities that students would find interesting enough to participate in and interact with their peers and teachers. Thus, this pedagogical innovation shows how two EFL teachers implemented a peer feedback strategy to foster online interaction. The outcomes point to new strategies as well as pedagogical possibilities to motivate students' interaction when working in online environments. El creciente desarrollo tecnológico ha creado nuevas prácticas pedagógicas en el aula de clase de inglés como lengua extranjera para maximizar el tiempo en ambientes virtuales. Por trabajar en un contexto pedagógico donde se están implementando nuevas tecnologías, algunos profesores se preocuparon por promover la interacción y participación en línea de estudiantes universitarios en la clase inglés. Dado que fue difícil diseñar y llevar a cabo actividades en línea para que los estudiantes participaran e interactuaran con sus compañeros y maestros, el artículo expone en qué consistió la innovación pedagógica que dos profesoras de inglés implementaron como estrategia de realimentación para fomentar la interacción en línea. Los resultados reflejan la necesidad de crear nuevas estrategias y posibilidades pedagógicas para motivar la interacción de los estudiantes cuando trabajan en entornos virtuales.